Smartphone Addiction dan Hubungan Sosial dalam Keluarga (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
A smartphone is a tool for communication with the broader community. Users can operate a cellphone according to their will, have more complex device functions on the screen's surface, and have a much more sophisticated operating system. Smartphone addiction is when someone is too dependent on using a smartphone to access the internet continuously without thinking about the adverse effects. The excessive use of smartphones will have a negative impact; parents should be closer to their children, but it can be seen that parents hold smartphones more often but ignore their children. This study aims to look at the correlation between smartphones and social relations within the family. This research method is a quantitative type using a product moment correlational design. The population and sample are 167 active students at the Faculty of Health Sciences, the University of Muhammadiyah Palopo, in 2022. The data analysis technique used is Spearman's correlation test. The study results show a correlation between smartphone Addiction and the quality of social relations in the family (p-value = 0.000 <α value = 0.05). The strength of the relationship in the weak category and the direction of the correlation is negative, which means that the higher the smartphone use among students, the lower the social relationship. in the family.